Особливості онтоморфогенезу Delphinium sergii Wissjul. в умовах культури у Національному ботанічному саду ім. М.М. Гришка НАН України - Gnatiuk, А.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The ontomorphogenesis of endemic species of eastern Black Sea Coast – Delphinium sergii Wissjul. is studied. The results of this species study in M.M. Gryshko National Botanical Garden are given. Onthogenic states of cultivated individuals of D. sergii are described. It is established that the individuals of D. sergii ex situ accelerate the ontogenetic development and reach the generative state for 2 year. Thus juvenile period lasts for one growing season. It is noted that under the influence of unfavorable factors (thickened crops, drought, shading) development of individuals D. sergii became slower. Particulation, caused vegetative self-reproduction of populations, is characteristic for studied plants.